Bioavailability of a novel form of silicon supplement. Issue 1 (December 2018) - Scholey, D.; Belton, D.; Burton, E.; Perry, C.
Abstract In this study, we assessed uptake and potential efficacy of a novel, pH neutral form of silicon supplementin vitro and using broiler chickens as a model species.In vitro bioavailability of this supplement was significantly higher than other commercial supplements tested, all of which claim available silica content. To confirm bioavailability of the new supplementin vivo, a broiler chick feeding trial reported blood uptake that was significantly higher than a Bamboo-derived silicon supplement. We assessed dose response of the novel supplement in a further study with increased dose related levels of silicon being detected in the blood and tibia. We found tibia and foot ash residue as a percentage of dry mass was higher with inclusion of the novel supplement in the diet, particularly in young birds and that this was followed by significant increase in tibia breaking strength. This novel supplement may therefore have applications in the improvement of bone integrity, with implications for the reduction of lameness in broilers. These results indicate the novel silica supplement is readily absorbed in chicks, and transported in the blood supply to sites such as the skeleton due to it being present in a non-condensed, monomeric form. There is potential for wider application of this silica supplement in other species where bone breakages are a problem, including high performance sport.